A Review of French Spelling Guide and French Writing - Somayeh Zokhtareh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The close relationship between spelling and writing has led us to study Mahvash Ghavimi’s works as a part of studies done at the Institute for Humanities and Cultural Studies, and we review and criticize two educational and academic works entitled "The French Spelling Guide" and "The French Writing Guidelines", published by the University Publication Center. The present article has tried to take a brief look at the emergence and evolution of spelling before paying attention to the role of dictation in learning French language spelling and its connection with writing skill.The study of the content and especially the exercises that the authors have included in these two books has allowed this research to reveal the approach of the authors of the books in language teaching by determining the type of exercises, and also there are some strategies suggested in order to correct, improve and update them. The main goal of the authors in these two books is to teach the basics of French spelling in a very prescriptive way in the first book, and in the second one, it refers to sentence construction and its constituent elements to be learned by bachelor students of French language and literature and French language translation.